Síntese de Mg2NiH4 para armazenagem de hidrogênio em compósito polimérico - Matheus, Felipe Henrique (2021)
In this work, powder production routes based on Mg2NiH4 are investigated, utilizing high-energy reactive milling; thermal treatment procedures, and hydrogen absorption/desorption cycles, which promote controlled decrepitation, capable of storing and releasing hydrogen at 250 °C, maintaining a high absorption capacity. This material was utilized to obtain a Mg2NiH4-PMMA metal-polymer composite with a maximum work temperature of 250 °C due to possible degradation of PMMA at higher temperatures. The production of this composite aims to create a protective barrier with the polymer, blocking contaminants such as O2 e H2O presents in the atmosphere. The composite production routes were investigated, using high-energy reactive milling with and without the addition of THF solvent. It was verified that the high-energy reactive milling, followed by thermal treatment procedures and controlled decrepitation, can be utilized to produce Mg2NiH4 with the desired properties. Using these techniques, a material based on Mg2NiH4 was obtained with an absorption capacity of 3.5 wt. % at 300 °C and 3 wt. % at 250 °C and with good hydrogen absorption kinetics, reaching absorption plateaus in less than a minute in some cases, so this route was considered ideal to the production of the storage metallic material to be utilized in the metal-polymer composite. However, the results from the production of storage metal-polymer composites by the milling techniques are inconclusive, indicating that more studies are necessary to evaluate these production techniques.